Long Run Performance of Initial Public Offerings in India - Agarwal, Nikhil (2007)
This research evaluates the short and long run performance of initial public offerings which were issued during the period of 2001 and 2004 in India. In my work I have emphasized more on the long run performance which is measured by using methodologies such as Cumulative Abnormal Return (CAR) and Buy and Hold Abnormal Return (BHAR). Regression analysis was used in order to find out whether performance can be predicted or not by looking at the various firm characteristics. It was found that the age and industry type are the most significant predictors of IPO long term performance. Empirical evidence on initial public offerings showed that IPOs mostly under perform in the long run while this research contradicts them by showing an over performance. A comparison has been made with the other researches in order to find out the reason behind this difference.